The Urgency of Human Rights Protection in the Digital Age in the Perspective of Data Security and Privacy - Phireri, Phireri (IJBLE Scientific Publications Community Inc., 2024)
This research aims to provide a better understanding of current technological developments, how the challenges of the digital era can affect human rights and how the law can be used as a tool to protect these rights. This research also explains cases of human rights violations related to data security and privacy, as well as looking for legal solutions that can help maintain a balance between technological progress and human rights. This research was prepared using a literacy approach or literature review using various secondary library sources to answer all problems in the research carried out.